An analysis of illocutionary act in the main character utterances in SOUL movie - Panji As'adi; Taufiq Effendi (Mitra Palupi, 2022)
Background: Some people not only use language in communication, but also use actions. It occurs in the movie through dialogue.Dialogue is not usually realized as a written text spoken by an actor or character in a movie Purpose: The purpose of this research is to find out the types of illocutionary acts do the utterances of the main character in Soul movie convey. Design and methods: This study uses a descriptive and qualitative method because the data in this study are words rather than numbers. Results: Researchers classified 137 illocutionary acts in soul movie scripts and found that there are four categories, which are 54 data for representative types (40%), 59 data for directive types (43%), and 10 data for commissive types (7%), and the expression type with 14 data (10%). The directive type shows the highest percentage, and the commissive type shows the lowest percentage. Throughout the analysis of the data, declarative type is not founded by the main character in the movie.